Challenges to Women's Active Political Participation in Northern Nigeria: The Interplay of Education, Religious-Cultural Norms, and Financial Barriers - Fidelis, Freda (Religion and Policy Journal, 2025)
Research Problem: Women's political participation in Northern Nigeria faces multilayered barriers rooted in the interaction between limited educational access, religious-cultural norms, and economic restrictions. Despite constitutional guarantees of gender equality, structural inequalities persist, undermining women’s agency in public life. Deeply entrenched patriarchal systems and practices such as the Kulle system continue to restrict women’s visibility and participation in political processes. These challenges raise fundamental concerns about gender inclusion in Nigeria’s democratic governance and the realization of Sustainable Development Goal 5 (Gender Equality). Research Purposes: This study seeks to analyze the underlying factors that hinder women’s active political engagement in Northern Nigeria, with a focus on the intersecting roles of education, religious-cultural traditions, and economic constraints. Grounded in liberal feminist theory and equity theory, the research aims to explain how systemic inequalities—manifested through social norms, limited access to quality education, and economic marginalization—constrain women’s opportunities for political participation and leadership. Research Methods: The study employs a qualitative and analytical approach, utilizing thematic content analysis of secondary data drawn from peer-reviewed journal articles, policy reports, and institutional documents. Sources are selected to capture the lived experiences of Northern Nigerian women across educational, cultural, and economic dimensions. The method emphasizes interpretive analysis to identify recurring themes, causal relationships, and structural mechanisms that perpetuate women’s exclusion from political life. Results and Discussion: Findings reveal that educational disparities significantly limit women’s civic literacy, confidence, and leadership capacity, making it difficult for them to navigate political spaces. Religious and cultural traditions, particularly those emphasizing female seclusion such as Kulle, restrict women’s mobility and visibility in public affairs. Economic constraints, including high campaign costs, privatized party financing, and inadequate institutional support, further marginalize women aspiring to leadership roles. These dimensions are interlinked, collectively reinforcing systemic exclusion and limiting women’s empowerment. The analysis underscores that without addressing the root causes—educational inequality, patriarchal cultural values, and economic disenfranchisement—efforts to promote women’s political representation will remain superficial and unsustainable. Research Implications and Contributions: This study contributes to the broader discourse on gender-sensitive governance by demonstrating how intersecting social, cultural, and economic factors create cumulative disadvantages for women in politics. It recommends multi-level interventions such as expanding access to quality education for girls, engaging religious and traditional leaders to foster cultural reorientation, and instituting legal frameworks requiring political parties to subsidize female candidacies. Furthermore, the research advocates for institutional reforms and financial inclusion initiatives to empower women economically and politically. By integrating feminist and equity perspectives, the study advances understanding of structural gender inequality in Northern Nigeria and provides practical insights for policymakers, civil society organizations, and scholars committed to achieving gender equality in political participation.